2011
DOI: 10.1371/journal.pone.0027332
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Arterial-Venous Plasticity in Adult Neovascularization

Abstract: ObjectiveProper arterial and venous specification is a hallmark of functional vascular networks. While arterial-venous identity is genetically pre-determined during embryo development, it is unknown whether an analogous pre-specification occurs in adult neovascularization. Our goal is to determine whether vessel arterial-venous specification in adult neovascularization is pre-determined by the identity of the originating vessels.Methods and ResultsWe assessed identity specification during neovascularization by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…In addition, after in vivo implantation, MF-based constructs were able to generate vessels with specific arterio-venous phenotypes, as characterised by the presence of either EphrinB2 or EphB4 positive vessels (arterial and venous identity, respectively) (Fig. 2C) [62]. Analysis of vessel arterio-venous plasticity using MFs obtained from transgenic reporter mice and a magnetic bead isolated method to harvest MFs of arterial identity revealed that arterial-venous identity in adult neovascularization is not necessarily pre-determined and that adult microvessels display a considerable level of phenotypic plasticity during neovascularization, with microvessels of arterial identity being able to give rise to full neovasculature containing both arterial and venous microvessels [62].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, after in vivo implantation, MF-based constructs were able to generate vessels with specific arterio-venous phenotypes, as characterised by the presence of either EphrinB2 or EphB4 positive vessels (arterial and venous identity, respectively) (Fig. 2C) [62]. Analysis of vessel arterio-venous plasticity using MFs obtained from transgenic reporter mice and a magnetic bead isolated method to harvest MFs of arterial identity revealed that arterial-venous identity in adult neovascularization is not necessarily pre-determined and that adult microvessels display a considerable level of phenotypic plasticity during neovascularization, with microvessels of arterial identity being able to give rise to full neovasculature containing both arterial and venous microvessels [62].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…2C) [62]. Analysis of vessel arterio-venous plasticity using MFs obtained from transgenic reporter mice and a magnetic bead isolated method to harvest MFs of arterial identity revealed that arterial-venous identity in adult neovascularization is not necessarily pre-determined and that adult microvessels display a considerable level of phenotypic plasticity during neovascularization, with microvessels of arterial identity being able to give rise to full neovasculature containing both arterial and venous microvessels [62]. These MF-based constructs have been shown to display blood perfusion in vivo as early as 2 days post implantation [61].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessels that were initially capillaries can turn into larger conductance vessels (and vice versa) at any location within the developing network. Redistribution of flow directions can cause transitions from venous to arterial vessel type in response to the resulting hemodynamic and metabolic conditions (22,53), and flow conditions can thus determine vascular identity (17,43).…”
Section: Reviewsmentioning
confidence: 99%
“…While hemodynamics most certainly are critical in establishing mature, stable vessel and network phenotypes, there is possibly some genetic predetermination operating in concert with or independent of hemodynamic cues, particularly during development [101]. However, there is considerable arterio-venous plasticity in ECs and microvessels [102,103], suggesting that the level of genetic predetermination might be limited in the adult.…”
Section: Implantationmentioning
confidence: 99%